2016
DOI: 10.1186/s12913-016-1625-x
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship care and support following treatment for breast cancer: a multi-ethnic comparative qualitative study of women’s experiences

Abstract: BackgroundAs the number of breast cancer survivors continues to rise, Western populations become more ethnically and socially diverse and healthcare resources become ever-more stretched, follow-up that focuses on monitoring for recurrence is no longer viable. New models of survivorship care need to ensure they support self-management and are culturally appropriate across diverse populations. This study explored experiences and expectations of a multi-ethnic sample of women with breast cancer regarding post-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 42 publications
3
24
0
11
Order By: Relevance
“…The qualitative findings converge with results yielded from the quantitative study. Congruent with previous research, the reported unmet needs are mostly related to information provision as well as accessibility and continuity of care . Our findings also corroborate the results of a systematic review, which indicated that cancer patients continued to need information about treatment and about recovery during the posttreatment period .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The qualitative findings converge with results yielded from the quantitative study. Congruent with previous research, the reported unmet needs are mostly related to information provision as well as accessibility and continuity of care . Our findings also corroborate the results of a systematic review, which indicated that cancer patients continued to need information about treatment and about recovery during the posttreatment period .…”
Section: Discussionsupporting
confidence: 84%
“…In line with previous literature, our findings suggest that not all cancer patients are alike in their need for information and some patients may prefer not to be informed . In this respect, personalized needs assessment and provision of customized information are warranted . A few of the women raised concerns over financial barriers incurred by the additional costs associated with long‐term follow‐up and/or endocrine therapy, as well as decreased capability at work.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the existing qualitative researches, 6–8 focus groups are generally included, with 6–8 participants in each group [ 28 , 29 ]. In this study, 8 focus groups were included with 8 participants in each group.…”
Section: Methodsmentioning
confidence: 99%